VISCOELASTIC DAMPING SYSTEMS FOR ENHANCED SEISMIC PERFORMANCE OF REINFORCED CONCRETE BEAMS (FUDMA JOURNAL OF SCIENCES, 2025)
This research investigates the effectiveness of Viscoelastic Damping Systems (VDS) in enhancing the seismic performance of reinforced concrete (RC) beams. To evaluate this, a series of numerical simulations were conducted using time-history seismic analysis, incorporating earthquake magnitudes ranging from moderate to severe (e.g., 5.5 to 7.5 on the Richter scale). The RC beams analyzed were standard-sized with a span of 4 meters, designed per conventional seismic codes, while VDS parameters, such as damping ratio and placement, were optimized for maximum energy dissipation. A control group of RC beams without VDS was included to provide a baseline for performance comparisons. The study focuses on critical performance metrics, including displacement control, energy dissipation, and residual deformation, to assess the impact of VDS under varying seismic loads. Results indicate that the integration of VDS reduces displacement by 25% to 30%, increases energy dissipation by 50% to 67%, and decreases residual deformation by up to 40%, compared to the control group. While these findings highlight the significant benefits of VDS, the results are particularly applicable to mid-sized RC beams commonly used in low- to mid-rise structures and may require further validation for larger or highly irregular designs. These findings demonstrate that VDS significantly improve the seismic resilience of RC beams by absorbing and dissipating seismic energy, thereby reducing the risk of structural damage and permanent deformation. The study emphasizes the importance of integrating VDS in seismic design codes for RC structures in earthquake-prone regions, while advocating for future research to optimize their use across...
Keywords: Viscoelastic damping system; Seismic performance; Energy dissipation; Seismic resilience; Reinforced concrete (RC) beams